The Role Of Digital Interactive Boards In Enhancing Mathematics Learning Motivation On Trigonometry Material In Vocational High School: A Self-Determination Theory Perspective - Suwarni, Suwarni; Jumintono, Jumintono; Mulyono, Rahmat (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Mathematics learning in vocational high schools still faces motivational challenges, especially in trigonometry, because the topic requires visualization, logical reasoning, and conceptual understanding. This study aims to analyze the role of Digital Interactive Boards (DIBs/PID) in enhancing Grade XI students’ mathematics learning motivation on trigonometry material at SMK Negeri 1 Muntok from the perspective of Self-Determination Theory. A descriptive qualitative approach was employed by involving one mathematics teacher and twelve Grade XI students selected purposively based on their involvement in learning activities using DIBs. Data were collected through semi-structured interviews, classroom observation, and documentation, and were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings show that before the use of DIBs, students experienced difficulty in understanding trigonometric concepts, showed low interest, and tended to be passive in classroom activities. After DIBs were implemented, students’ motivation increased, as indicated by stronger attention, higher interest, more active participation, and greater confidence to solve problems in front of the class. Visualization, interactive multimedia, digital quizzes, immediate feedback, and direct screen interaction helped students understand abstract trigonometric concepts in a more concrete and engaging way. From the perspective of Self-Determination Theory, this motivational improvement occurred because DIBs supported the fulfillment of students’ basic psychological needs for competence, autonomy, and relatedness. The study concludes that DIBs function not only as instructional media but also as pedagogical instruments that create interactive, meaningful, and student-centered mathematics learning experiences.